Implementasi Algoritma C4.5 Pada Sistem Evaluasi Perijinan Pembukaan Program Studi - Ibnu Akil (LPPM Universitas Bina Sarana Informatika, 2017)
C4.5 algorithm is one of machine learning algorithms which have been used widely for expert systems. C4.5 algorithm has been admitted and has a high accuracy in decision making cases based on classes and multiple attributes. The algorithm which is proposed by J. Ross Quinlan in 1993 will be implemented in one of expert system that is permission evaluation of new study program in Kemenristek Dikti.